Agricultural Experimentation in Cotton Cultivation under Natural and Climatic Conditions of Southern Russia (1920s-1940s) - E. N. Badmaeva (Научный диалог)
This article examines the intricacies of cotton production organization in Southern Russia during the 1930s. It analyzes the progression and outcomes of cotton planting and harvesting campaigns amid challenging natural and climatic conditions. A comparative analysis of cotton sowing practices in Kalmykia and Dagestan is presented. The findings indicate that non-irrigated cotton farming developed more intensively in the former region, while irrigated cotton cultivation thrived in Dagestan, which had ample water resources. It is concluded that the increase in cotton production in Southern Russia during this period primarily resulted from the expansion of cultivated areas. The study demonstrates that pre-war Southern Russian cotton farming did not meet practical expectations and failed to provide the country with sufficient raw cotton. Archival documents serve as the primary materials for this research, introducing previously unpublished resources into the academic discourse. The relevance and practical significance of this study lie in the fact that the historical experience of cotton sowing in Southern Russia can inform contemporary agricultural development in the country.